Laser-assisted management of peripheral ossifying fibroma: Perplexity in diagnosis - Gayathri Somashekar; Yamini Rajachandrasekaran; Sumathi H Rao; Geetha Thirugnanasambandam; Deepa Chandrashekaraiah (Wolters Kluwer Medknow Publications, 2022)
Peripheral ossifying fibroma (POF) is the most common reactive gingival lesion. The cause and pathology are well understood. Peripheral giant cell granuloma, pyogenic granuloma, fibroma, and peripheral fibroma are among the differential diagnoses. The confirmed diagnosis for POF is based on histopathological evidence. A healthy 49-year-old man with fibrous swelling in the lower left anterior region of his jaw is discussed in this case report. Excisional biopsy was performed utilizing a diode laser in pulse mode at 980 nm. The patient was monitored for a year, and there was no recurrence.